Subsurface Ocean Warming Hotspots and Potential Impacts on Marine Species: The Southwest South Atlantic Ocean Case Study - Franco, Bárbara C.; Combes, Vincent; González Carman, Victoria (Frontiers in Marine Science, 2020)
In the southwest South Atlantic Ocean (SWAO) strong ocean surface warming hotspots have been observed mainly along the path of the Brazil Current (BC), Brazil-Malvinas Confluence (BMC), and in the Río de la Plata (RdlP). However, there is no knowledge about the signature of ocean hotspots below the surface and the potential effects of ocean warming on marine biota. In this work, we provide initial evidence of how deep the hotspots of the SWAO extend in the water column, in particular at mid-water and bottom layers where two marine species ‒the green turtle (Chelonia mydas) and the Patagonian scallop (Zygochlamys patagonica)‒ inhabit. We compare 15 years (2003–2017) of Copernicus Marine Environment Monitoring Service (CMEMS) ARMOR3D high‐resolution (1/4°) 3-D temperatures reprocessed from combined satellite and in-situ observations with high‐resolution (1/12°) Mercator ocean reanalysis. We also use location data of C. mydas and Z. patagonica to discuss the potential impacts of warming on these species in terms of geographic distribution, phenological shifts and thermal tolerance. The potential distribution of C. mydas changes in relation to the sea surface temperature (SST) and the bathymetry. The warming of the whole water column in the RdlP (> 0.4°C/decade) and the southward movement of the mean surface isotherms, which likely drove turtle displacements, could enable the opening up of novel optimal thermal habitats and/or a longer seasonal residency for the species. At the BMC, warming is driven by the southward displacement of the BC during the past decades. Ocean model temperature indicates cooling/warming in deep waters along the outer shelf and shelf break regions, which vary according the displacements of the BMC. The expected warming of the waters over the Patagonian scallop largest bed could exceed the thermal tolerance of this species and its survival. Given the lack of long-term monitoring programs to address the impacts of climate change on marine biota in the SWAO, our results provide the first effort to call the attention of stakeholders and decision makers on marine conservation and fishery management to work towards better management strategies in the context of climate change.